Knowledge Management and Empowering Professional Learning Communities based on Buddhist Principles: The Dimension of Sappurisa Dhamma - Nilkote, Reongwit; Singsorn, Natataporn; Saisena, Natthapat; Sukpom, Thitiwas; Papan, Nattakorn (ASEAN Journal of Religious and Cultural Research, 2024)
Knowledge management is a crucial process that supports the development of organizations into learning organizations, emphasizing collaboration and teamwork to achieve the highest quality outcomes. The principles of Sappurisa-dharma, rooted in Buddhist teachings, play a significant role in effectively developing both individuals and groups. There are seven components: 1. Dhammaññutā: Establishing a shared understanding of the essence of Dhamma among members. 2. Atthaññutā: Understanding shared goals to ensure that members have clear objectives and can effectively support one another, fostering a collective understanding of the organization and its objectives. 3. Attaññutā: Encouraging self-awareness, which promotes the development of skills suited to each individual recognizing strengths and weaknesses allows for appropriate management and enhances teamwork effectiveness. 4. Mattaññutā: Mindful utilization of resources. 5. Kālaññutā: Effective time management through systematic planning and organization, which leads to smooth and efficient operations. 6. Parissaññutā: Creating a supportive atmosphere through strong interpersonal relationships. 7. Puggalaññutā: Understanding individual members to foster positive relationships within the group, creating an open environment where members support one another. In the context of a community of practice, knowledge management plays an essential role in generating new knowledge and promoting the exchange of experiences applying the principles of Sappurisa-dhamma helps members adapt better by fostering collaboration and learning from shared experiences. This approach enables organizations to develop sustainably and effectively respond to societal needs in any situation.